2020
DOI: 10.3390/jcm9113514
|View full text |Cite
|
Sign up to set email alerts
|

Early Retinal Changes by OCT Angiography and Multifocal Electroretinography in Diabetes

Abstract: Background: To evaluate the earliest retinal morphological and functional changes in diabetic eyes without or with early signs of diabetic retinopathy (DR). Methods: Twenty-two eyes with no DR (noDR group), 22 eyes with mild DR (DR group), and 18 healthy nondiabetic eyes (controls) were enrolled. All eyes were studied by means of spectral domain optical coherence tomography (OCT), OCT angiography (OCTA), and multifocal electroretinogram (mfERG). Results: A significantly higher number of OCT hyperreflective int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…Using OCT, OCTA, and OP, the present study found that both retinal structural and vascular changes as well as functional ones are precociously present in diabetic eyes, compared to healthy controls, in accordance to previous reports, and that they are related to each other [14,19]. In particular, we found a reduction of VLF and FD of the intraretinal vascular networks at OCTA, representing the length and complexity of retinal microvessels, in diabetic patients with no or early signs of DR, as previously reported [14]. Moreover, we confirmed the presence of early OPs alterations in diabetic eyes compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using OCT, OCTA, and OP, the present study found that both retinal structural and vascular changes as well as functional ones are precociously present in diabetic eyes, compared to healthy controls, in accordance to previous reports, and that they are related to each other [14,19]. In particular, we found a reduction of VLF and FD of the intraretinal vascular networks at OCTA, representing the length and complexity of retinal microvessels, in diabetic patients with no or early signs of DR, as previously reported [14]. Moreover, we confirmed the presence of early OPs alterations in diabetic eyes compared to healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…OCT and OCTA were performed using the Spectralis HRA + OCT2 platform (Heidelberg Engineering, Heidelberg, Germany), as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…OCTA provides microvasculature images with higher contrast and better resolution than with fluorescein angiography; furthermore, it contributes to the quantitative evaluation of retinal microvasculature [2]. Currently, OCTA images and quantitative parameters, such as vessel density (VD), have become important markers for retinal disease, and the detailed information of blood flow it provides has contributed greatly to the early detection of multiple eye diseases [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have reported that denoised images show lower background noise and higher image quality than that of single-scan images of the macular area [11,14], the influence of denoising using commercially available devices on the qualitative and quantitative parameters of the images of both macular and optic areas has not been investigated. The VD is considered an important marker for the early detection of multiple eye diseases; for example, the VD in the macular area can help detect retinal damage in patients with diabetes and hypertension at an early stage, and the VD in the optic area can help in the early diagnosis of glaucoma [3][4][5]. Thus, the VD in both macular and optic areas acquired from denoised images needs to be verified as credible data before its application in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%